Significance of Aurora B overexpression in hepatocellular carcinoma. Aurora B Overexpression in HCC - Lin, Zhong-Zhe (BioMed Central, 2010)
BACKGROUND: To investigate the significance of Aurora B expression in hepatocellular carcinoma (HCC). METHODS: The Aurora B and Aurora A mRNA level was measured in 160 HCCs and the paired nontumorous liver tissues by reverse transcription-polymerase chain reaction. Mutations of the p53 and β-catenin genes were analyzed in 134 and 150 tumors, respectively, by direct sequencing of exon 2 to exon 11 of p53 and exon 3 of β-catenin. Anticancer effects of AZD1152-HQPA, an Aurora B kinase selective inhibitor, were examined in Huh-7 and Hep3B cell lines. RESULTS: Aurora B was overexpressed in 98 (61%) of 160 HCCs and in all 7 HCC cell lines examined. The overexpression of Aurora B was associated with Aurora A overexpression (P = 0.0003) and p53 mutation (P = 0.002) and was inversely associated with β-catenin mutation (P = 0.002). Aurora B overexpression correlated with worse clinicopathologic characteristics. Multivariate analysis confirmed that Aurora B overexpression was an independent poor prognostic factor, despite its interaction with Aurora A overexpression and mutations of p53 and β-catenin. In Huh-7 and Hep3B cells, AZD1152-HQPA induced proliferation blockade, histone H3 (Ser10) dephosphorylation, cell cycle disturbance, and apoptosis. CONCLUSION: Aurora B overexpression is an independent molecular marker predicting tumor invasiveness and poor prognosis of HCC. Aurora B kinase selective inhibitors are potential therapeutic agents for HCC treatment.